Integration of World Literary Traditions and Innovative Artistic Searches in Contemporary Kazakh Prose - Rita B. Sultangaliyeva; Sandugash S. Sagidulliyeva; Zinulla Zh. Mutiyev; Gulnaz S. Sagynadin; Aidarbek A. Akbulatov; Gauhar S. Askarova; Kamshat B. Zhumasheva (Forum for Linguistic Studies, 2024)
This paper aims to explore the ways, in which contemporary Kazakh prose writers create innovative texts characterized by hybridity peculiar to the era of postmodernism. In our study, we view the prose in contemporary Kazakhstan as a phenomenon of glocalization, since it combines global trends in postmodern literature with an original local flavor. Drawing on the short stories by five distinguished young prose authors and using narrative, hermeneutic and comparative methods of analysis, we identify innovative forms of dealing with social problems and universal values, as well as conveying the characters’ inner feeling in contemporary Kazakh artistic prose. We provide examples of the influence of global artistic techniques on Kazakh literary works and their integration with Kazakh folklore to reflect the fate of the Kazakh people during the period of political and social instability in the country during the transitional period. The results of the qualitative analysis show that young prose authors’ creativity forms a new color by integrating national folklore motifs with traditions of world literature based on Gothic and mystical themes. Through hybrid texts based on references to terror and mysticism, they raise issues of national identity and national code in their own unique styles incorporating mythopoetic expressions.